Ethnographically Derived Socio-technical Analysis for Information System Support in Intensive Home Care - Markus Jelonek; Thomas Herrmann; Michael Ksoll; Nina Altmann (Complex Systems Informatics and Modeling Quarterly)
Developing information systems and collaboration support in the field of intensive home care is faced with challenging conditions of empirical work for requirements elicitation. On the one hand, the huge variety of aspects and situation-related characteristics require a deliberate analysis and close interaction with caregivers and relatives to identify the needs and constraints of technical support. On the other hand, the relevant places are hardly accessible. To be able to visit and observe the clients in situ, consent is needed by the caregiver, the client, and the relatives living with them, and a high level of privacy and confidentiality has to be maintained. Based on an ethnographical data gathering and analysis, this article provides a comprehensive categorization that characterizes the work of caregivers in intensive home, to make the work of information system designers in this field more efficient: activities, interpersonal interaction, documentation, qualification, interaction with technology, client autonomy, history of medical records, and feedback on intensive home care. Finally, these categories are compared with related work of socio-technical design of health care information systems.